Kesulitan Belajar pada Siswa Anak Berkebutuhan Khusus (ABK) di Sekolah Dasar Negeri Inklusi BA 4 - Maya Rahma Sarita; Ahmad Saufi Al-Hadisi; Bagus Setiawan (AR-RIAYAH : Jurnal Pendidikan Dasar, 2023)
This study aims to determine learning difficulties in students with special needs. The learning difficulties experienced by children are caused by the unstable psychological condition of the children. This study used a qualitative approach with interview, observation, and documentation techniques. This research was conducted at Inclusion BA 4 Public Elementary School. The results of this study indicated that grade 3 ABK students at Inclusion BA 4 Public Elementary School had different learning difficulties. Among them are caused by slow learner disorders, hyperactivity, and intellectual disability.